2018
DOI: 10.1186/s40104-018-0252-2
|View full text |Cite
|
Sign up to set email alerts
|

Gas stunning with CO2 affected meat color, lipid peroxidation, oxidative stress, and gene expression of mitogen-activated protein kinases, glutathione S-transferases, and Cu/Zn-superoxide dismutase in the skeletal muscles of broilers

Abstract: BackgroundMeat color and lipid peroxidation are important traits related to meat quality. CO2 concentration is a critical factor that can affect meat quality in the commercial use of gas stunning (GS). However, the effect and mechanism of CO2 stunning on meat color and lipid peroxidation during long-term storage remain poorly studied. We aimed to study the effects of GS methods, especially CO2 concentration, on meat color and meat lipid peroxidation in broilers during long-term storage at 4 °C and to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…The MDA level in the groups of control, E90V, and E120V all decreased at d 4 as compared with d 0 (p < 0.05) in the present study (Table 2). This is consistent with the changes of MDA level in breast meat at d 1 and d 9 [10] and in thigh meat at d 6 as compared with d 0 [20] in electrically stunned broilers. The decrease of MDA concentration may be due to further metabolisms of MDA through enzymatic and chemical reactions, resulting in the products of thromboxane A 2, acetaldehyde, acetate, or Schiff-base adducts as time went on [21,22].…”
Section: Lipid Oxidative Stabilitysupporting
confidence: 89%
See 1 more Smart Citation
“…The MDA level in the groups of control, E90V, and E120V all decreased at d 4 as compared with d 0 (p < 0.05) in the present study (Table 2). This is consistent with the changes of MDA level in breast meat at d 1 and d 9 [10] and in thigh meat at d 6 as compared with d 0 [20] in electrically stunned broilers. The decrease of MDA concentration may be due to further metabolisms of MDA through enzymatic and chemical reactions, resulting in the products of thromboxane A 2, acetaldehyde, acetate, or Schiff-base adducts as time went on [21,22].…”
Section: Lipid Oxidative Stabilitysupporting
confidence: 89%
“…Different from geese, previous studies of our team demonstrated that the MDA level in breast meat of broilers was not affected by ES methods [10] or controlled atmosphere stunning (CAS) methods at day 0 (d 0) [20]. Whereas when the refrigeration time was prolonged, MDA levels at day 1 (d 1) and day 3 (d 3) were increased by low-current and high-frequency combination compared to high-current and low-frequency combination [10], or by CAS with 40% CO 2 compared to 79% CO 2 at d 3 [20]. These differences among studies may be due to different ES variables, body resistance (geese vs. broilers), and measured tissues (liver vs. muscle).…”
Section: Lipid Oxidative Stabilitymentioning
confidence: 74%
“…MDA decreased to the minimum level from d 0 to d 6 and recovered to the level of d 0 again in d 9 in the raw thigh meat of both ES‐treated birds ( P < 0.01, Table ), indicating a similar lipid oxidative stability in thigh meat between treatment LHES and treatment HLES. This tendency was similar with the breast meat from the same broilers treated by the same stunning methods (Xu et al , ) or similar with thigh meat from broilers stunned by controlled atmosphere stunning (Xu et al , ). Differently, Alvarado et al () reported an increase of MDA level from d 1 to d 4 (cooked breast meat) in broilers that were treated with different stunning methods.…”
Section: Resultssupporting
confidence: 75%
“…This was similar to the breast muscle, as pre‐slaughter LHES also stimulated oxidative stress and transcriptionally activated the MAPK/Nrf2/GST pathway (Xu et al , ). In contrast to the effects of ES, gas stunning with CO 2 slightly suppressed the transcription of GSTA3, GSTT1 and SOD1 in the breast muscle but not in thigh muscle (Xu et al , ). These differences may be due to different biochemical and electrophysiological responses to CO 2 stunning and electrical stunning in thigh muscles of broilers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation